Environmental factors affecting honey bees (Apis cerana) and cabbage white butterflies (Pieris rapae) at urban farmlands - Lee, Myung-Bok (PeerJ, 2023)
Rapid urbanization results in a significantly increased urban population, but also the loss of agricultural lands, thus raising a concern for food security. Urban agriculture has received increasing attention as a way of improving food access in urban areas and local farmers’ livelihoods. Although vegetable-dominant small urban farmlands are relatively common in China, little is known about environmental factors associated with insects that could affect ecosystem services at these urban farmlands, which in turn influences agricultural productivity. Using Asian honey bee (Apis cerana) and cabbage white butterfly (Pieris rapae) as examples, I investigated how environmental features within and surrounding urban farmlands affected insect pollinator (bee) and pest (butterfly) abundance in a megacity of China during winters. I considered environmental features at three spatial scales: fine (5 m-radius area), local (50 m-radius area), and landscape (500 m-raidus and 1 km-radius areas). While the abundance of P. rapae increased with local crop diversity, it was strongly negatively associated with landscape-scale crop and weed covers. A. cerana responded positively to flower cover at the fine scale. Their abundance also increased with local-scale weed cover but decreased with increasing landscape-scale weed cover. The abundance of A. cerana tended to decrease with increasing patch density of farmlands within a landscape, i.e., farmland fragmentation. These results suggest that cultivating too diverse crops at urban farmlands can increase crop damage; however, the damage may be alleviated at farmlands embedded in a landscape with more crop cover. Retaining a small amount of un-harvested flowering crops and weedy vegetation within a farmland, especially less fragmented farmland can benefit A. cerana when natural resources are scarce.
Keywords: Ecosystem service; Pest; Pollinator; Small farmland; Urban agriculture; Weed; Farmland fragmentation